Evaluation of e-commerce location and entry to China: Implications on shipping and trade - Yulia Panova; Albert Wee Kwan Tan; Olli-Pekka Hilmola; M. H. Puvindran; Hongsheng Xu; Weidong Li (Journal of Shipping and Trade (JST), 2019)
E-commerce is experiencing strong global growth, and leading market is nowadays that of China, whether it is evaluated from the perspective of domestic market size or cross-border volumes. In this research work further understanding and knowledge is built from Chinese market using general choice algorithm (GCA) and two real-life case studies. The outcome of GCA model shows the list of the most preferable locations for e-commerce enterprise development. Findings of this study are also compared to two case studies of e-commerce entrance to Chinese market, where one of these two is operating in an omnichannel environment. Market entrance in these two was implemented through very simplified and centralized distribution structure, and using location of Shanghai. Actual operations are either outsourced or in-house produced. Cash on delivery (COD) is still the preferred payment method in e-commerce order fulfilment. One factor being rather important in case companies was distribution prices, where courier services all over the country play an important role. For logistics in general, and sea ports, research reveals that currently dominating areas of the Pearl and Yangtze River Delta face the challenge to some extent from other places of China as favourable locations for e-commerce and consumption are also at north and western parts.
Keywords: 650; E-commerce; Omnichannel; Decision-making; Warehouses; China